Economic Burden On The Women Of Pari Island - Isatou Sallah; Hariati Sinaga (MUWAZAH : jurnal kajian gender, 2025)
Economic stress is a first-order problem disproportionately impacting women and hampered development. There is a large body of literature on the economic burden shouldered by women. However, literature specifically on women's financial burden in Pari Island is lacking. Furthermore, understanding women's agency and grassroots initiatives could provide localized insights and contribute to broader discussions. The investigation article utilizes a feminist political economy theory to examine women's economic burden. The qualitative research methodology used a case study centered on Pari Island women who faced financial hardship. The findings show that women on Pari Island faced economic difficulties, and the Island's women's group faced obstacles as the government refused to assist them because they were perceived as a dissident organization willing to oppose the government. In addition to promoting women's empowerment, this women's organization allegedly challenged the abuses their community experienced from the government and the mining company that the Suharto dictatorship sold their property. This article recommends that the government should resolve land disputes with foreign investors who claimed the Island was sold to them by the government. To alleviate the economic burden on Pari Island's fisherwomen and petty traders, measures like gender equality, fair trade conditions, equal access to credit and financial support, inclusive policies, and an understanding of women's rights are needed. Government and non-governmental organizations should provide more assistance such as skills and entrepreneurship training.